2011
DOI: 10.1021/jp110665j
|View full text |Cite
|
Sign up to set email alerts
|

Dipole Assisted Photogated Switch in Spiropyran Grafted Polyaniline Nanowires

Abstract: In this work we show dipole-assisted photogated switching by covalent grafting of photoactive molecules to conducting polymers. Photochromic spiropyran molecules were covalently attached to polyaniline (PANI) nanowires via N-alkylation reaction to the quinoic part of PANI. Upon irradiation with ultraviolet light spiropyran transformed to a large dipole containing molecule, merocyanine form. We show that this transformation leads to a substantial (ca. 2 orders of magnitude) increase in conductance of the photoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 45 publications
0
29
0
Order By: Relevance
“…Crivillers et al reported a similar attempt [107]; an azobenzene-SAM at the electrode– N , N ′-1H,1H-perfluorobutyl dicyanoperylenecarboxydiimide (PDIF-CN 2 ) interface induced a variation in the carrier injection barrier to result in I on / I off = 2.0. Additionally, azobenzene or spiropyran were attached to the surface of low-dimensional materials: graphene, carbon nanotubes, and polymer nanowires [108110]. In these cases, photochromic molecules are near the carrier flow, and therefore photochromism can influence the drain current.…”
Section: Light-receiving Ofetsmentioning
confidence: 99%
“…Crivillers et al reported a similar attempt [107]; an azobenzene-SAM at the electrode– N , N ′-1H,1H-perfluorobutyl dicyanoperylenecarboxydiimide (PDIF-CN 2 ) interface induced a variation in the carrier injection barrier to result in I on / I off = 2.0. Additionally, azobenzene or spiropyran were attached to the surface of low-dimensional materials: graphene, carbon nanotubes, and polymer nanowires [108110]. In these cases, photochromic molecules are near the carrier flow, and therefore photochromism can influence the drain current.…”
Section: Light-receiving Ofetsmentioning
confidence: 99%
“…Materials with photochromic SPs have the advantage of reversibly photo‐induce changes in their properties such as conductivity,24, 28, 45 wetting behaviour,9, 11, 22 optical properties,9, 23, 27, 31, 32, 35, 44, 46 metal ion complexation,7–10 cell adhesion,25 surface morphology,9 association/solubility,29, 30 mechanical effects,21, 36 colloidal system stability17, 38 and membrane permeability 15, 16. Therefore, the possibility to photo‐induce such a variation in their physical and chemical properties, has made SP‐based materials widely utilised in biological applications,25 non‐linear optics,47 reversible optical memory,24, 48 optoelectronics49 and chemical sensing 7, 10, 13, 46, 50.…”
Section: Introductionmentioning
confidence: 99%
“…A large variety of applications for photoresponsive molecules has been investigated in highlevel technologies such as controlling the conformation and activity of biomolecules [1][2][3], sensors [4][5][6][7][8][9][10], data recording, optical storage, optical switching [11][12][13][14], displays, non-linear optics [15][16][17][18], and other photochemical and photophysical reactions [19,20].…”
Section: Introductionmentioning
confidence: 99%